Interfacial Reactions and Smooth Etching Strategy of n-type Gallium Nitride Photoanodes. Issue 16 (21st December 2020) - Hu, Huiqing; Guo, Sai; Wang, Yahui; Shi, Kang
Abstract : While photoelectrochemical etching is the only efficient wet-etching method for manufacturing n-type gallium nitride (GaN)-based devices, the current technology cannot simultaneously achieve nanoscale surface roughness (Ra) and flatness. We proposed a smooth etching strategy through the depth study of the interfacial reactions of GaN photoanodes in organic deep eutectic solvents (DESs) and aqueous electrolytes. The results show that with the increase of GaN photoanode potential, first hydroxyl anions and then H2 O molecules capture ultraviolet (UV)-photogenerated holes ( h + ) at the GaN surface/interface, initiating GaN oxidation by generating hydroxyl radical (OH·) surface intermediates. The etching results from the synergic effects of interfacial reactions, including GaN oxidation, oxide film formation and dissolution, and side reactions. Only the synergic effects in weak acidic electrolytes (e.g., pH = 2.3) can minimize roughening influences without bending the oxide film. Such etching can prepare the most typical groove structure of GaN-based devices (e.g., insulated gate bipolar transistor) with a nanoscale surface flatness. The Ra reaches 3.28 nm, and the etching rate attains 10.78 nm·min −1 .